The genus Anisocentropus McLachlan (Trichoptera, Calamoceratidae) in Japan - Ito, Tomiko; Hayashi, Yumiko; Shimura, Noriyoshi (Zootaxa, 2012)
We reviewed the Japanese species of Anisocentropus McLachlan (Trichoptera, Calamoceratidae) and confirmed 3 species, Anisocentropus (Anisocentropus) kawamurai (Iwata, 1927), A. (A.) pallidus (Martynov, 1935) and A. (A.) magnificus Ulmer, 1907. The last species is recorded from Japan for the first time. For clear comparisons, adult and immature stages of the three species are described based on associations established by rearing larvae. The male, female and pupa of A. (A.) kawamurai, female and pupa of A. (A.) pallidus and female and immature stages of A. (A.) magnificus are newly described. Anisocentropus (A.) minutus (Martynov, 1930), known from southeastern Asia, is synonymized with A. (A.) kawamurai (Iwata, 1927).